Patterns of appearance and risk of misdiagnosis of intrahepatic cholangiocarcinoma in cirrhosis at contrast enhanced ultrasound. (27th February 2013) - Galassi, Marzia; Iavarone, Massimo; Rossi, Sandro; Bota, Simona; Vavassori, Sara; Rosa, Laura; Leoni, Simona; Venerandi, Laura; Marinelli, Sara; Sangiovanni, Angelo; Veronese, Letizia; Fraquelli, Mirella; et al.
Abstract Aim Primary aim was to validate the percentage of intrahepatic cholangiocarcinomas (ICC) which have a contrast vascular pattern at contrast enhanced ultrasound (CEUS) at risk of misdiagnosis with hepatocellular carcinoma (HCC) and, secondary aim, to verify if any characteristics in the CEUS pattern helps to identify ICC. Methods All ICC on cirrhosis seen in three Italian centres (Bologna, Milan and Pavia) between 2003 and 2011, in which CEUS and at least another imaging technique (CT or MRI) had been performed, were retrospectively identified. Those patients with ICC size comparable to the early HCC stage (Milan criteria, considered as small ICC) were enrolled for this study. The enhancement pattern at CEUS was analysed and compared with CT or MRI. Results A total of 25 small ICC made this study group. CEUS was at risk of misdiagnosis of ICC for HCC in a significantly higher number of cases than in CT (performed in 24 ICC) (52% vs. 4.2%, P = 0.009) and MRI (11 ICC) (52% vs. 9.1%, P = 0.02). A different contrast pattern among all techniques was found in 6 of 10 ICC lesions submitted to the three imaging methods. In the arterial phase, ICC lacked global hyperenhacement in approximately 50% of cases at CEUS and the degree of intensity of wash‐out in the late phase was marked in 24% of nodules. Conclusions CEUS misdiagnosed as HCC a significantly higher number of ICC lesions in cirrhotic patients than CT and MRI. However, some CEUS contrast features can help suspect ICC, especially in some cases with inconclusive CT or MRI.